2008
DOI: 10.1021/nl0723634
|View full text |Cite
|
Sign up to set email alerts
|

Single-Walled Carbon Nanotubes Can Induce Pulmonary Injury in Mouse Model

Abstract: Carbon nanotubes are a nanomaterial that is extensively used in industry. The potential health risk of chronic carbon nanotubes exposure has been raised as of great public concern. In the present study, we have demonstrated that intratracheal instillation of 0.5 mg of single-walled carbon nanotubes (SWCNT) into male ICR mice (8 weeks old) induced alveolar macrophage activation, various chronic inflammatory responses, and severe pulmonary granuloma formation. We then used Affymetrix microarrays to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
170
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(175 citation statements)
references
References 40 publications
5
170
0
Order By: Relevance
“…In other hand, it is possible that nanomaterials generate inflammatory responses in intracellular location. For example, CNTs can induce oxidative stress and increase proinflammatory cytokines and antiapoptotic gene expression by activating various transcription factors such as nuclear factor κB and activator protein 1 and overproduction of TNF-a by macrophages (Muller et al, 2005;Chou et al, 2008). It has been sufficiently demonstrated that maternal inflammation may induce adverse effects in fetal neurodevelopment (Mahmood et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In other hand, it is possible that nanomaterials generate inflammatory responses in intracellular location. For example, CNTs can induce oxidative stress and increase proinflammatory cytokines and antiapoptotic gene expression by activating various transcription factors such as nuclear factor κB and activator protein 1 and overproduction of TNF-a by macrophages (Muller et al, 2005;Chou et al, 2008). It has been sufficiently demonstrated that maternal inflammation may induce adverse effects in fetal neurodevelopment (Mahmood et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to inhalation exposure, intratracheal instillation typically delivers a higher dose to animals. 64 [65][66][67]73,74 and fibrotic lung injury. 65 After intratracheal instillation, nanoparticles were taken up by both the alveolar macrophages and the alveolar epithelial cells.…”
Section: Respiratory Toxicitymentioning
confidence: 99%
“…That was the case of the study of multi-walled carbon nanotubes acting in a mouse model, where no induction of inflammation was showed, while macrophage activation and development of the inflammatory response was observed for single-walled carbon nanotubes. [14,15] In the last decade, a lot of methods for the synthesis of AuN with the defined parameters, such as size or shape was developed.…”
Section: Introductionmentioning
confidence: 99%